Application of Business Model Canvas at Thirty-One Collection Boutique - Setiyani, Lila; Risnawati; Tjandra, Evelyn (Lembaga KITA, 2022)
The fashion business today is one of the promised businesses. Thrity-One Collection Boutique is one of the business traders in the fashion sector that will be built in Karawang Regency. The purpose of this research is to develop a business strategy using the Business Model Canvas at Thirty-One Collection Boutique. The research method used is qualitative, data collection is done by interviewing fashion enthusiasts and fashion actors. This study analyzes the business model used by Thirty-One Collection Boutique using the Business Model Canvas, then analyzes each element using a SWOT analysis (Strength, Weakness, Opportunities, and Threats). The results of this study are a business strategy to increase productivity and see the risks that may be faced by the Thirty-One Collection Boutique Store and to help business actors to minimize the risks that may arise and find out the potential that can be developed in the Thirty-One Collection Boutique Store business.